(untitled) (Clinics, 2014)
OBJECTIVE: The association between rarely used anthropometric measurements (e.g., mid-upper arm, forearm, and calf circumference) and metabolic syndrome has not been proven. The aim of this study was to assess whether mid-upper arm, forearm, calf, and waist circumferences, as well as waist/height ratio and waist-to-hip ratio, were associated with metabolic syndrome. METHODS: We enrolled 387 subjects (340 women, 47 men) who were admitted to the obesity outpatient department of Istanbul Medeniyet University Goztepe Training and Research Hospital between September 2010 and December 2010. The following measurements were recorded: waist circumference, hip circumference, waist/height ratio, waist-to-hip ratio, mid-upper arm circumference, forearm circumference, calf circumference, and body composition. Fasting blood samples were collected to measure plasma glucose, lipids, uric acid, insulin, and HbA1c. RESULTS: The odds ratios for visceral fat (measured via bioelectric impedance), hip circumference, forearm circumference, and waist circumference/hip circumference were 2.19 (95% CI, 1.30-3.71), 1.89 (95% CI, 1.07-3.35), 2.47 (95% CI, 1.24-4.95), and 2.11(95% CI, 1.26-3.53), respectively. The bioelectric impedance-measured body fat percentage correlated with waist circumference only in subjects without metabolic syndrome; the body fat percentage was negatively correlated with waist circumference/hip circumference in the metabolic syndrome group. All measurements except for forearm circumference were equally well correlated with the bioelectric impedance-measured body fat percentages in both groups. Hip circumference was moderately correlated with bioelectric impedance-measured visceral fat in subjects without metabolic syndrome. Muscle mass (measured via bioelectric impedance) was weakly correlated with waist and forearm circumference in subjects with metabolic syndrome and with calf circumference in subjects without metabolic syndrome. CONCLUSION: Waist circumference was not linked to metabolic syndrome in obese and overweight subjects; however, forearm circumference, an unconventional but simple and appropriate anthropometric index, was associated with metabolic syndrome and bioelectric impedance-measured visceral fat, hip circumference, and waist-to-hip ratio.